Seawater-salt-mist-resistant corrosion-resistant cable and preparation method thereof

By using 3-(2-thienyl)acrylic acid, diethylenedimethacrylate and modified anti-UV agent in the outer protective layer of the cable, the corrosion of the cable in the humid and heat and high salt spray environment is solved. The problem of this problem achieves higher resistance to seawater salt spray and corrosion resistance, extends cable life and reduces failure rate and safety hazards.

CN119410057APending Publication Date: 2025-02-11JIANGSU DIYI GROUP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411539892.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

Existing cables are prone to shell corrosion in environments with humid and heat and high salt spray concentrations, resulting in reduced conductivity and frequent failures, affecting the quality of power transmission and bringing safety hazards.

Method used

The composite modified polyolefin made of 3-(2-thienyl)acrylic acid, diethylene dimethacrylate, modified anti-UV agent and polyethylene are used as the outer protective layer, and the large side group and The thiophene structure improves the shear, impact and antibacterial properties of the cable, and improves the UV resistance by modifying the anti-UV agent.

Benefits of technology

It significantly improves the cable's seawater salt spray resistance and corrosion resistance, extends the service life of the cable, reduces the failure rate and safety hazards, and improves the overall strength and mechanical properties of the cable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005112533130000071
    Figure BDA0005112533130000071
Patent Text Reader

Abstract

The invention discloses a seawater salt mist-resistant corrosion-resistant cable and a preparation method thereof, and relates to the technical field of corrosion-resistant cables. According to the invention, 3-(2-thienyl) acrylic acid, diethylene glycol dimethacrylate, a modified anti-ultraviolet agent and polyethylene are copolymerized to prepare modified polyolefin, a large side group is introduced into a main chain to form a non-coplanar structure, the distance and free volume between molecular chains are increased, the shearing resistance and impact resistance of the cable are improved, meanwhile, a thiophene structure can hinder bacterial replication, and the anti-ultraviolet performance of the cable is improved. And in cooperation with a long chain segment of diethylene glycol dimethacrylate, interaction and wrapping among polymer chain segments are reduced, the flexibility of polymer chains is improved, and the overall strength of the cable is improved. According to the modified anti-ultraviolet agent, 4-chloromethyl benzoic acid is combined with 4-(2-allyl)-catechol, a benzophenone structure is formed, the anti-ultraviolet performance is achieved, meanwhile, chlorine elements in the 4-chloromethyl benzoic acid have high resistance to acid and alkali chemical substances, and the anti-corrosion effect is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of corrosion-resistant cables, in particular to a seawater salt spray corrosion-resistant cable and a preparation method thereof. Background Art

[0002] Power cables are widely used in various working scenarios, and civil cables are closely related to our lives. Cable connectors are electrical products that connect cables to form a continuous path. With the development of cities, the widespread use of cables in power grid systems, and the commissioning of various high-power equipment, power transmission has a safety issue that cannot be ignored. Once the conductivity of the cable decreases or a failure occurs, it will affect the quality of power transmission. In severe cases, it may even lead to the decoupling of the power system, causing economic losses and endangering people's lives. According to statistics, more than half of the total number of power supply accidents are related to cable failures, a large part of which is caused by cable casing corrosion. In the southern coastal areas, the humid and hot environment with high salt fog concentration is more likely to affect the performance and life of the cable casing, causing frequent cable overheating failures.

[0003] Usually, wire and cable materials are made of plastic and rubber materials as base resins, stabilizers, plasticizers, inorganic fillers, additives, lubricants and other additives, and are kneaded, mixed and extruded to prepare particles. Among them, polyolefins are the most common plastic materials. However, the wire and cable sheaths made of polyolefins have poor light and heat stability, weak UV protection, and insufficient anti-aging performance. Especially for outdoor cables, under the influence of factors such as wind, rain, sunlight (ultraviolet rays), heat, ozone, and bacterial erosion, it is easy to cause macromolecular chain breakage and harmful changes in chemical structure, premature aging, brittleness, cracking and other phenomena, so that their physical and mechanical properties deteriorate or even lose their insulation and protective functions, causing certain potential dangers and posing great hidden dangers to the safety of society and people's lives and property. Summary of the invention

[0004] The object of the present invention is to provide a seawater salt spray corrosion resistant cable and a preparation method thereof, so as to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a seawater salt spray corrosion resistant cable, which comprises a copper core, a polyethylene insulation layer, and a composite modified polyolefin outer protective layer from inside to outside.

[0006] Furthermore, the composite modified polyolefin outer protective layer is prepared by copolymerizing 3-(2-thienyl) acrylic acid, diethylene glycol dimethacrylate, a modified anti-ultraviolet agent and polyethylene.

[0007] Furthermore, the modified anti-ultraviolet agent is prepared from 4-chloromethylbenzoic acid and 4-(2-allyl)-catechol.

[0008] Furthermore, a method for preparing a seawater salt spray and corrosion resistant cable comprises the following preparation steps:

[0009] (1) 12 to 18 parts of 4-chloromethylbenzoic acid, 15 to 23 parts of 4-(2-allyl)-catechol, and 144 to 220 parts of chlorobenzene are uniformly mixed, 1.6 to 2.8 parts of aluminum chloride are added, and the mixture is reacted at 100 to 120° C. and 80 rpm for 4 to 6 hours to obtain a reaction solution, which is purified to obtain a modified anti-ultraviolet agent;

[0010] (2) Under a nitrogen atmosphere, 14 to 22 parts of 3-(2-thienyl) acrylic acid, 11 to 19 parts of diethylene glycol dimethacrylate, 8 to 12 parts of a modified anti-ultraviolet agent, 2 to 4 parts of triethanolamine, and 70 to 128 parts of toluene are mixed uniformly at 80 rpm, ethylene gas is introduced until the pressure reaches 3 MPa, the temperature is raised to 70 to 80° C., and the reaction is carried out for 6 to 10 hours. During the reaction, ethylene gas is continuously introduced to maintain a constant pressure. After the reaction is completed, the air is connected to obtain a reaction solution, which is purified to obtain a composite modified polyolefin;

[0011] (3) 48-62 parts of composite modified polyolefin, 4-6 parts of carbon black and 1-3 parts of antioxidant are mixed evenly, and then extruded and granulated at a head temperature of 175-195°C, a screw speed of 170-190 r / min, an extrusion pressure of 9-11 MPa and a shear rate of 190-220 s -1 , obtaining composite modified polyolefin particles;

[0012] (4) 47 to 61 parts of polyethylene, 3 to 5 parts of zinc stearate, and 4 to 6 parts of flame retardant are mixed evenly, melt-extruded and coated with an oxygen-free copper core at 175 to 185° C. to form a 1.8 mm insulating layer, then 86 to 110 parts of composite modified polyolefin particles are added, melt-extruded and coated with an insulating layer at 175 to 195° C. to form a 5.0 mm outer protective layer, and the temperature is reduced to 30° C. at 60° C. / min to obtain a seawater salt spray and corrosion resistant cable.

[0013] Furthermore, the purification step of step (1) is as follows: adding 1 part of the reaction solution to 10-20 parts of an aqueous sodium hydroxide solution, stirring at 80 rpm for 10 minutes, filtering the filtrate, then adding an aqueous hydrochloric acid solution to the filtrate until the pH is 6-7, filtering the solid, washing it with deionized water for 3 times, and drying it in an oven at 50-60°C for 8-12 hours.

[0014] Furthermore, the content of sodium hydroxide in the sodium hydroxide aqueous solution is 10wt%; and the concentration of the hydrochloric acid aqueous solution is 2mol / L.

[0015] Furthermore, the purification step in step (2) is as follows: filter 1 part of the reaction solution, take the solid, add 15 to 35 parts of ethyl acetate, stir at 90 rpm for 35 to 45 minutes, filter the filtrate, and concentrate at a vacuum degree of -0.08 MPa and 40°C for 3 to 5 hours.

[0016] Furthermore, the antioxidant in step (3) is any one of nano-silicon dioxide, lignin, and AO-1076.

[0017] Furthermore, the model of the polyethylene in step (4) is any one of XLPE-LAB011 and XLPE-LXC101; the cross-sectional area of ​​the oxygen-free copper core is 5mm 2 .

[0018] Furthermore, the flame retardant in step (4) is any one of melamine, aluminum hydroxide and phosphate ester.

[0019] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0020] The invention prepares the modified polyolefin by co-participating 3-(2-thienyl) acrylic acid, diethylene glycol dimethacrylate and a modified anti-ultraviolet agent in the polymerization process of polyethylene, introduces a large side group into the main chain to form a non-coplanar structure, reduces the interaction and close stacking between polymer molecular chains, increases the distance between molecular chains and the free volume, thereby indirectly improving the shear resistance of the cable and improving the impact resistance of the cable. Meanwhile, the thiophene structure can combine with bacteria and DNA to hinder their replication, thereby causing the death of bacteria and achieving an antibacterial effect. The longer chain segment of diethylene glycol dimethacrylate increases the movement space, reduces the interaction and wrapping between polymer chain segments, improves the flexibility of the polymer chain, and thus improves the overall strength of the cable.

[0021] Among them, the modified anti-ultraviolet agent combines 4-chloromethylbenzoic acid with 4-(2-allyl)-catechol to form a benzophenone structure. When exposed to ultraviolet rays, the molecules undergo thermal motion, and the hydrogen bonds in the chelate ring formed by the carbonyl group and hydrogen bonds in benzophenone are destroyed, converting the ultraviolet light energy into heat energy and releasing it back to its original state, thereby improving the anti-ultraviolet performance. At the same time, the chlorine element in 4-chloromethylbenzoic acid has a high resistance to many acids, alkalis and other chemical substances, thereby achieving a corrosion-resistant effect. On this basis, the allyl group introduced by 4-(2-allyl)-catechol can jointly participate in the polymerization reaction of polyethylene, embedded in the molecular chain segments, and further enhance the mechanical properties of the cable. DETAILED DESCRIPTION

[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0023] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the seawater salt spray corrosion resistant cables prepared in the following examples are as follows:

[0024] Tensile strength before aging: Take the embodiment and comparative example of the same size and test them according to GB / T 2951.

[0025] Tensile strength after aging: Take the embodiment and the comparative example of the same length, use a 6kW xenon lamp for irradiation and spray water at a water pressure of 0.12-0.15MPa, and perform periodic ultraviolet irradiation according to a cycle of 120 minutes, of which 18 minutes are for simultaneous water spraying and light irradiation, and the other 120 minutes are for light alone, for a total exposure of 2000 hours. Then, the sample is placed at room temperature for 20 hours, and the tensile strength test is performed with reference to GB / T 2951.

[0026] Antibacterial rate: Take the same size of the embodiment and the comparative example and test them according to QB / T 2591.

[0027] Corrosion resistance: Take the embodiment and the comparative example of the same size, soak them in 20wt% hydrochloric acid solution, 20wt% sodium hydroxide solution, 20wt% sodium chloride solution and aqueous solution under the same conditions for 168h, take them out and observe the surface corrosion.

[0028] Example 1

[0029] (1) 12 parts of 4-chloromethylbenzoic acid, 15 parts of 4-(2-allyl)-catechol, and 144 parts of chlorobenzene were mixed uniformly, 1.6 parts of aluminum chloride were added, and the mixture was reacted at 100° C. and 80 rpm for 4 hours to obtain a reaction solution. 1 part of the reaction solution was added to 10 parts of a 10 wt% sodium hydroxide aqueous solution, and the mixture was stirred at 80 rpm for 10 minutes. The filtrate was filtered to obtain the filtrate, and a 2 mol / L hydrochloric acid aqueous solution was then added to the filtrate to a pH of 6. The solid was filtered to obtain the solid, and the solid was washed with deionized water for 3 times, and dried in an oven at 50° C. for 8 hours to obtain a modified UV inhibitor;

[0030] (2) Under a nitrogen atmosphere, 14 parts of 3-(2-thienyl)acrylic acid, 11 parts of diethylene glycol dimethacrylate, 8 parts of a modified anti-ultraviolet agent, 2 parts of triethanolamine, and 70 parts of toluene were mixed uniformly at 80 rpm, ethylene gas was introduced until the pressure reached 3 MPa, the temperature was raised to 70°C, and the reaction was carried out for 6 hours. During the reaction, ethylene gas was continuously introduced to maintain the pressure unchanged. After the reaction was completed, the air was connected to obtain a reaction liquid, 1 part of the reaction liquid was filtered, a solid was taken, 15 parts of ethyl acetate was added, and the mixture was stirred at 90 rpm for 35 minutes. The filtrate was filtered and concentrated at a vacuum degree of -0.08 MPa and 40°C for 3 hours to obtain a composite modified polyolefin;

[0031] (3) 48 parts of composite modified polyolefin, 4 parts of carbon black and 1 part of nano-silicon dioxide were mixed evenly, and extruded into granules after mixing. The head temperature was 175°C, the screw speed was 170r / min, the extrusion pressure was 9MPa, and the shear rate was 190s -1 , obtaining composite modified polyolefin particles;

[0032] (4) Mix 47 parts of XLPE-LAB011 polyethylene, 3 parts of zinc stearate, and 4 parts of melamine, and melt and extrude them at 175°C to form a coating with a cross-sectional area of ​​5 mm 2 An oxygen-free copper core is added to form a 1.8 mm insulation layer, and then 86 parts of composite modified polyolefin particles are added, melted and extruded at 175°C to coat the insulation layer to form a 5.0 mm outer protective layer, and then the temperature is reduced to 30°C at 60°C / min to obtain a seawater salt spray and corrosion-resistant cable.

[0033] Example 2

[0034] (1) 15 parts of 4-chloromethylbenzoic acid, 19 parts of 4-(2-allyl)-catechol, and 182 parts of chlorobenzene were mixed uniformly, 2.2 parts of aluminum chloride were added, and the mixture was reacted at 110° C. and 80 rpm for 5 h to obtain a reaction solution. 1 part of the reaction solution was added to 15 parts of a 10 wt % sodium hydroxide aqueous solution, and the mixture was stirred at 80 rpm for 10 min. The filtrate was filtered to obtain the filtrate. A 2 mol / L hydrochloric acid aqueous solution was then added to the filtrate to a pH of 6.5. The solid was filtered to obtain the solid, and the solid was washed with deionized water for 3 times and dried in an oven at 55° C. for 10 h to obtain a modified UV inhibitor.

[0035] (2) Under a nitrogen atmosphere, 18 parts of 3-(2-thienyl)acrylic acid, 15 parts of diethylene glycol dimethacrylate, 10 parts of a modified anti-ultraviolet agent, 3 parts of triethanolamine, and 99 parts of toluene were mixed uniformly at 80 rpm, ethylene gas was introduced until the pressure reached 3 MPa, the temperature was raised to 75°C, and the reaction was carried out for 8 hours. During the reaction, ethylene gas was continuously introduced to maintain the pressure unchanged. After the reaction was completed, the air was connected to obtain a reaction liquid, 1 part of the reaction liquid was filtered, a solid was taken, 25 parts of ethyl acetate was added, and the mixture was stirred at 90 rpm for 40 minutes. The filtrate was filtered and concentrated at a vacuum degree of -0.08 MPa and 40°C for 4 hours to obtain a composite modified polyolefin;

[0036] (3) 55 parts of composite modified polyolefin, 5 parts of carbon black and 2 parts of lignin were mixed evenly, and extruded into granules after mixing. The head temperature was 185°C, the screw speed was 180 r / min, the extrusion pressure was 10 MPa, and the shear rate was 205 s -1 , obtaining composite modified polyolefin particles;

[0037] (4) Mix 54 parts of XLPE-LXC101 polyethylene, 4 parts of zinc stearate, and 5 parts of aluminum hydroxide, melt and extrude at 180°C to form a coating with a cross-sectional area of ​​5 mm 2 An oxygen-free copper core is added to form a 1.8 mm insulation layer, and then 98 parts of composite modified polyolefin particles are added, melted and extruded at 185°C to coat the insulation layer to form a 5.0 mm outer protective layer, and then the temperature is reduced to 30°C at 60°C / min to obtain a seawater salt spray and corrosion-resistant cable.

[0038] Example 3

[0039] (1) 18 parts of 4-chloromethylbenzoic acid, 23 parts of 4-(2-allyl)-catechol, and 220 parts of chlorobenzene were mixed uniformly, 2.8 parts of aluminum chloride were added, and the mixture was reacted at 120° C. and 80 rpm for 6 h to obtain a reaction solution. 1 part of the reaction solution was added to 20 parts of a 10 wt % sodium hydroxide aqueous solution, and the mixture was stirred at 80 rpm for 10 min. The filtrate was filtered to obtain the filtrate. A 2 mol / L hydrochloric acid aqueous solution was then added to the filtrate to a pH of 7. The solid was filtered to obtain the solid, and the solid was washed with deionized water for 3 times and dried in an oven at 60° C. for 12 h to obtain a modified UV inhibitor.

[0040] (2) Under a nitrogen atmosphere, 22 parts of 3-(2-thienyl)acrylic acid, 19 parts of diethylene glycol dimethacrylate, 12 parts of a modified anti-ultraviolet agent, 4 parts of triethanolamine, and 128 parts of toluene were mixed uniformly at 80 rpm, ethylene gas was introduced until the pressure reached 3 MPa, the temperature was raised to 80°C, and the reaction was carried out for 10 hours. During the reaction, ethylene gas was continuously introduced to maintain the pressure unchanged. After the reaction was completed, the air was connected to obtain a reaction liquid, 1 part of the reaction liquid was filtered, a solid was taken, 35 parts of ethyl acetate was added, and the mixture was stirred at 90 rpm for 45 minutes. The filtrate was filtered and concentrated at a vacuum degree of -0.08 MPa and 40°C for 5 hours to obtain a composite modified polyolefin;

[0041] (3) 62 parts of composite modified polyolefin, 6 parts of carbon black and 3 parts of AO-1076 were mixed evenly, and extruded into granules after mixing. The head temperature was 195°C, the screw speed was 190 r / min, the extrusion pressure was 11 MPa, and the shear rate was 220 s -1 , obtaining composite modified polyolefin particles;

[0042] (4) 61 parts of XLPE-LAB011 polyethylene, 5 parts of zinc stearate, and 6 parts of phosphate were mixed evenly and melted and extruded at 185°C to form a coating with a cross-sectional area of ​​5 mm 2 An oxygen-free copper core is used to form a 1.8 mm insulation layer, and then 110 parts of composite modified polyolefin particles are added, melted and extruded at 195°C to coat the insulation layer to form a 5.0 mm outer protective layer, and then the temperature is reduced to 30°C at 60°C / min to obtain a seawater salt spray and corrosion-resistant cable.

[0043] Comparative Example 1

[0044] The difference between Comparative Example 1 and Example 2 is that step (2) is different. Step (2) is changed to: in a nitrogen atmosphere, 15 parts of diethylene glycol dimethacrylate, 10 parts of modified anti-ultraviolet agent, 3 parts of triethanolamine, and 99 parts of toluene are mixed at 80 rpm, ethylene gas is introduced until the pressure is 3 MPa, the temperature is raised to 75°C, and the reaction is carried out for 8 hours. During the reaction, ethylene gas is continuously introduced to keep the pressure unchanged. After the reaction is completed, the air is connected to obtain a reaction liquid, 1 part of the reaction liquid is filtered, a solid is taken, 25 parts of ethyl acetate are added, and the mixture is stirred at 90 rpm for 40 minutes. The filtrate is filtered and concentrated at a vacuum degree of -0.08 MPa and 40°C for 4 hours to obtain a composite modified polyolefin. The remaining steps are the same as those in Example 2.

[0045] Comparative Example 2

[0046] The difference between Comparative Example 2 and Example 2 is that step (2) is different. Step (2) is changed to: in a nitrogen atmosphere, 18 parts of 3-(2-thienyl) acrylic acid, 10 parts of modified anti-ultraviolet agent, 3 parts of triethanolamine, and 99 parts of toluene are mixed at 80 rpm, ethylene gas is introduced until the pressure is 3 MPa, the temperature is raised to 75°C, and the reaction is carried out for 8 hours. During the reaction, ethylene gas is continuously introduced to keep the pressure unchanged. After the reaction is completed, the air is connected to obtain a reaction liquid, 1 part of the reaction liquid is filtered, a solid is taken, 25 parts of ethyl acetate are added, and the mixture is stirred at 90 rpm for 40 minutes. The filtrate is filtered and concentrated at a vacuum degree of -0.08 MPa and 40°C for 4 hours to obtain a composite modified polyolefin. The remaining steps are the same as those in Example 2.

[0047] Comparative Example 3

[0048] The difference between Comparative Example 3 and Example 2 lies in the difference between steps (2) and (3). Step (2) is changed to: in a nitrogen atmosphere, 18 parts of 3-(2-thienyl)acrylic acid, 15 parts of diethylene glycol dimethacrylate, 3 parts of triethanolamine, and 99 parts of toluene are mixed at 80 rpm, ethylene gas is introduced until the pressure reaches 3 MPa, the temperature is raised to 75°C, and the reaction is carried out for 8 hours. During the reaction, ethylene gas is continuously introduced to maintain the pressure unchanged. After the reaction is completed, air is connected to obtain a reaction solution. 1 part of the reaction solution is passed through a Filter, take the solid, add 25 parts of ethyl acetate, stir at 90rpm for 40min, filter and take the filtrate, concentrate at vacuum degree -0.08MPa and 40℃ for 4h to obtain a composite modified polyolefin; step (3) is changed to: 55 parts of composite modified polyolefin, 10 parts of modified anti-ultraviolet agent, 5 parts of carbon black and 2 parts of lignin are mixed evenly, and the mixture is extruded and granulated at a head temperature of 185℃, a screw speed of 180r / min, an extrusion pressure of 10MPa and a shear rate of 205s. -1 The remaining steps are the same as those in Example 2.

[0049] Comparative Example 4

[0050] The difference between Comparative Example 4 and Example 2 is that there is no step (1), and step (2) is changed to: in a nitrogen atmosphere, 18 parts of 3-(2-thienyl) acrylic acid, 15 parts of diethylene glycol dimethacrylate, 10 parts of 4-(2-allyl)-catechol, 3 parts of triethanolamine, and 99 parts of toluene are mixed at 80 rpm, ethylene gas is introduced until the pressure is 3 MPa, the temperature is raised to 75°C, and the reaction is carried out for 8 hours. During the reaction, ethylene gas is continuously introduced to keep the pressure unchanged. After the reaction is completed, the air is connected to obtain a reaction liquid, 1 part of the reaction liquid is filtered, a solid is taken, 25 parts of ethyl acetate are added, and the mixture is stirred at 90 rpm for 40 minutes. The filtrate is filtered and concentrated at a vacuum degree of -0.08 MPa and 40°C for 4 hours to obtain a composite modified polyolefin. The remaining steps are the same as those in Example 2.

[0051] Comparative Example 5

[0052] The difference between Comparative Example 5 and Example 2 is that there is no step (1), and step (2) is changed to: in a nitrogen atmosphere, 18 parts of 3-(2-thienyl) acrylic acid, 15 parts of diethylene glycol dimethacrylate, 10 parts of 4-chloromethylbenzoic acid, 3 parts of triethanolamine, and 99 parts of toluene are mixed at 80 rpm, ethylene gas is introduced until the pressure is 3 MPa, the temperature is raised to 75°C, and the reaction is carried out for 8 hours. During the reaction, ethylene gas is continuously introduced to keep the pressure unchanged. After the reaction is completed, the air is connected to obtain a reaction liquid, 1 part of the reaction liquid is filtered, a solid is taken, 25 parts of ethyl acetate are added, and the mixture is stirred at 90 rpm for 40 minutes. The filtrate is filtered and concentrated at a vacuum degree of -0.08 MPa and 40°C for 4 hours to obtain a composite modified polyolefin. The remaining steps are the same as those in Example 2.

[0053] Effect example

[0054] Table 1 below shows the performance analysis results of seawater salt spray and corrosion resistant cables using Examples 1 to 3 of the present invention and Comparative Examples 1 to 5.

[0055] Table 1

[0056]

[0057] From the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 1, it can be found that the thiophene structure of 3-(2-thienyl) acrylic acid can bind to bacteria and DNA, hinder their replication, thereby causing bacterial death and having an antibacterial effect. At the same time, copolymerization with ethylene can introduce large side groups into the main chain to form a non-coplanar structure, which reduces the interaction and close stacking between polymer molecular chains, increases the distance between molecular chains and the free volume, and improves the mechanical strength of the cable. From the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 2, it can be found that diethylene glycol dimethacrylate has a longer chain segment, which increases the space for movement, reduces the interaction and wrapping between polymer chain segments, improves the flexibility of the polymer chain, and improves the overall strength of the cable. By comparing the experimental data of Examples 1, 2, and 3 with those of Comparative Example 3, it can be found that the anti-ultraviolet agent is involved in the copolymerization reaction of ethylene and can be embedded in the molecular chain segment to enhance the mechanical properties of the cable; by comparing the experimental data of Examples 1, 2, and 3 with those of Comparative Examples 4 and 5, it can be found that 4-chloromethylbenzoic acid is combined with 4-(2-allyl)-catechol to form a benzophenone structure. When irradiated with ultraviolet light, the molecules undergo thermal motion, and the hydrogen bonds formed by the chelate rings in the carbonyl groups and hydrogen bonds in the benzophenone are destroyed, and the ultraviolet light energy is converted into heat energy and released and returns to the original state, thereby improving the anti-ultraviolet performance. At the same time, the chlorine element in 4-chloromethylbenzoic acid has a high resistance to many chemical substances such as acids and alkalis, thereby achieving a corrosion-resistant effect.

[0058] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A seawater salt spray and corrosion resistant cable, characterized in that: The seawater salt spray corrosion resistant cable comprises a copper core, a polyethylene insulation layer and a composite modified polyolefin outer protective layer from inside to outside.

2. The seawater salt spray and corrosion resistant cable according to claim 1, characterized in that: The composite modified polyolefin outer protective layer is prepared by copolymerizing 3-(2-thienyl) acrylic acid, diethylene glycol dimethacrylate, a modified anti-ultraviolet agent and polyethylene.

3. The seawater salt spray and corrosion resistant cable according to claim 2, characterized in that: The modified anti-ultraviolet agent is prepared from 4-chloromethylbenzoic acid and 4-(2-allyl)-catechol.

4. A method for preparing a seawater salt spray and corrosion resistant cable, characterized in that: The method comprises the following preparation steps: (1) 12 to 18 parts of 4-chloromethylbenzoic acid, 15 to 23 parts of 4-(2-allyl)-catechol, and 144 to 220 parts of chlorobenzene are uniformly mixed, 1.6 to 2.8 parts of aluminum chloride are added, and the mixture is reacted at 100 to 120° C. and 80 rpm for 4 to 6 hours to obtain a reaction solution, which is purified to obtain a modified anti-ultraviolet agent; (2) Under a nitrogen atmosphere, 14 to 22 parts of 3-(2-thienyl) acrylic acid, 11 to 19 parts of diethylene glycol dimethacrylate, 8 to 12 parts of a modified anti-ultraviolet agent, 2 to 4 parts of triethanolamine, and 70 to 128 parts of toluene are mixed uniformly at 80 rpm, ethylene gas is introduced until the pressure reaches 3 MPa, the temperature is raised to 70 to 80° C., and the reaction is carried out for 6 to 10 hours. During the reaction, ethylene gas is continuously introduced to maintain a constant pressure. After the reaction is completed, the air is connected to obtain a reaction solution, which is purified to obtain a composite modified polyolefin; (3) 48-62 parts of composite modified polyolefin, 4-6 parts of carbon black and 1-3 parts of antioxidant are mixed evenly, and then extruded and granulated at a head temperature of 175-195°C, a screw speed of 170-190 r / min, an extrusion pressure of 9-11 MPa and a shear rate of 190-220 s -1 , obtaining composite modified polyolefin particles; (4) 47 to 61 parts of polyethylene, 3 to 5 parts of zinc stearate, and 4 to 6 parts of flame retardant are mixed evenly, melt-extruded and coated with an oxygen-free copper core at 175 to 185° C. to form a 1.8 mm insulating layer, then 86 to 110 parts of composite modified polyolefin particles are added, melt-extruded and coated with an insulating layer at 175 to 195° C. to form a 5.0 mm outer protective layer, and the temperature is reduced to 30° C. at 60° C. / min to obtain a seawater salt spray and corrosion resistant cable.

5. The method for preparing a seawater salt spray and corrosion resistant cable according to claim 4, characterized in that: The purification step in step (1) is as follows: adding 1 part of the reaction solution to 10 to 20 parts of an aqueous sodium hydroxide solution, stirring at 80 rpm for 10 minutes, filtering the filtrate, then adding an aqueous hydrochloric acid solution to the filtrate until the pH is 6 to 7, filtering the solid, washing it three times with deionized water, and drying it in an oven at 50 to 60° C. for 8 to 12 hours.

6. The method for preparing a seawater salt spray and corrosion resistant cable according to claim 5, characterized in that: The content of sodium hydroxide in the sodium hydroxide aqueous solution is 10wt%; the concentration of the hydrochloric acid aqueous solution is 2mol / L.

7. The method for preparing a seawater salt spray and corrosion resistant cable according to claim 4, characterized in that: The purification step in step (2) is as follows: filter 1 part of the reaction solution, take the solid, add 15 to 35 parts of ethyl acetate, stir at 90 rpm for 35 to 45 minutes, filter the filtrate, and concentrate at a vacuum degree of -0.08 MPa and 40°C for 3 to 5 hours.

8. The method for preparing a seawater salt spray and corrosion resistant cable according to claim 4, characterized in that: The antioxidant in step (3) is any one of nano-silicon dioxide, lignin, and AO-1076.

9. The method for preparing a seawater salt spray and corrosion resistant cable according to claim 4, characterized in that: The model of the polyethylene in step (4) is any one of XLPE-LAB011 and XLPE-LXC101; the cross-sectional area of ​​the oxygen-free copper core is 5mm 2 .

10. The method for preparing a seawater salt spray and corrosion resistant cable according to claim 4, characterized in that: The flame retardant in step (4) is any one of melamine, aluminum hydroxide and phosphate.